نأشب تايصوت ةرطلخا عئاضبلا لقن - United Nations (United Nations, 2020)
The Model Regulations cover the classification of dangerous goods and their listing, the use, construction, testing and approval of packagings and portable tanks, and the consignment procedures (marking, labelling, placarding and documentation). They aim at ensuring a high level of safety by preventing accidents to persons and property and damage to the environment during transport and, providing at the same time, a uniform regulatory framework which can be applied worldwide for national or international transport by any mode.